Research on narrow coal pillar width optimization and surround rock control in Shiquan mine - Rui Wang; Zhen Shi; Jiulin Fan; Yajun Wang; Yanghao Peng; Manchao He; Bo Zhang (Rock Mechanics Bulletin)
To address the issue of severe coal resource waste and substantial deformation of the surrounding rock caused by the retention of coal pillars for protective lanes during the excavation along the void of the 30108 working face at Shiquan Coal Mine, a study was conducted on the stress distribution of coal pillars and the deformation of surrounding rocks in the 30108 haulage roadway under different coal pillar widths and tunneling methods. Initially, theoretical calculations of coal pillar width in the goaf mining section were conducted. Subsequently, a numerical model was established to simulate and analyze the stress distribution of coal pillars and the deformation characteristics of surrounding rock under different coal pillar widths and tunnel layout methods. Finally, support schemes were proposed and verified through field application. The study indicates that the coal pillar width within the 30108 haulage roadway should not be less than 8.94 ​m; The failure of the coal pillar is primarily characterized by plastic shear failure within the pillar and tensile failure on both sides of the pillar, the deformation of the surrounding rock in the tunnel is mainly manifested as tensile failure of the roof and floor slabs and shear failure of the sidewalls, as the width of the coal pillar increases, the deformation of the surrounding rock on the surface of the tunnel within the pillar gradually decreases, and when the coal pillar width reaches 8–10 ​m, the deformation of the surrounding rock in the tunnel becomes stable; The field application has been effective.